Fiducial marker placement via conventional or electromagnetic navigation bronchoscopy (ENB): an interdisciplinary approach to the curative management of lung cancer. (3rd November 2014) - Hagmeyer, Lars; Priegnitz, Christina; Kocher, Martin; Schilcher, Burkhart; Budach, Wilfried; Treml, Marcel; Stieglitz, Sven; Randerath, Winfried
Abstract: Background and Aims: Conventional and electromagnetic navigation bronchoscopy (ENB) is generally used as a diagnostic tool in suspicious pulmonary nodules. The use of this technique for the placement of fiducial markers in patients with inoperable but early‐stage lung cancer could present an innovative approach enabling risk‐reduced therapy. Methods: We present seven clinical cases where conventional bronchoscopy and ENB were used as part of an experimental interdisciplinary approach to clinical management and therapy planning. In each case, we analyzed the clinical indication, endoscopic procedures and post‐interventional outcome. Results: In six patients (three females, three males) with peripheral non‐small cell lung cancer (NSCLC), stage cT1cN0cM0, surgery and conventional stereotactic radiation therapy was not possible because of end‐stage chronic obstructive pulmonary disease. ENB was used for fiducial marker placement prior to cyberknife radiotherapy. No procedure‐related complications were observed. Complete remission could be achieved in four cases, partial remission in two cases and no relevant complications induced by radiotherapy were observed. In one male patient, an endoluminal relapse in the right lower lobe was diagnosed following a right upper lobe resection for a NSCLC. The tumor could not be clearly identified by computerized tomography, so that the bronchoscopic placement of a fiducial marker in the tumor was performed in order to allow stereotactic radiochemotherapy, by which complete remission could be achieved. Conclusion: Fiducial marker placement may be an interesting bronchoscopic technique in the interdisciplinary therapeutic approach to inoperable early‐stage lung cancer. In the described cases, therapy planning was successful and no procedure‐related complications were observed.